Development Types Of The Good & Halal Food Industry In Indonesia - Kadir, Syahruddin; Awaluddin, Murtiadi; K, Amiruddin (Islamic Financial And Accounting Review, 2023)
This research to determines the type of development of the halal food industry in Indonesia. The growth of the halal industry with the lifestyle of the Indonesian people needs improvement and control from the perspective of Islamic financial institutions and partners of the Halal Product Guarantee Agency known as Halal Product Companion. The research method used is a qualitative descriptive method with an overview of the literature. Based on the results of the analysis, it can be interpreted that the development of the halal food industry can be increased through development in the fields of agro-industry, halal logistics, halal lifestyle Islamic boarding schools, exports through MEA, halal food e-commerce, halal organic and halal finance from Islamic banking. The role of Islamic banking includes providing financial services in terms of controlling halal products, playing a role in supervising companies providing halal logistics services, and playing a role in the literacy of halal products to the public. PPH is tasked with verifying and validating the halal process of business actors' products. With the integration of all parties involved, the halal food industry in Indonesia has better prospects in the future.